Understanding user's intention to the continued use of digital library: what are the roles of aesthetics and information quality? / Raja Alwi Raja Omar...[et al.] - Raja Omar, Raja Alwi; Abdul Rahman, Abd Latif; Mohd Paili, Shahruhaida Adayu; Md Yatim, Norhidayu; Alawi Idris, Ahmad Sufi; Mohammed Ghazali, Asmadi (Universiti Teknologi MARA, Kedah, 2017)
Digital library has been developed by many institutions around the world. The digital library can be considered as a new information system which brings many benefits to the users. The investigation towards the digital library is important and crucial to understand the reason why users accept and continue to use digital library. Users can search the information and available resources through the digital library website. It is important to know user's perception towards the aesthetics of the digital library. Apart from that, because digital library provides information to users, researchers also need to investigate the quality of information in digital library. This study has used Extending the Unified Theory of Acceptance and Use of Technology (UTAUT2) in order to know user's intention to continue using the digital library